2013
DOI: 10.1159/000351074
|View full text |Cite
|
Sign up to set email alerts
|

Metoprolol-Mediated Amelioration of Sympathetic Nerve Sprouting after Myocardial Infarction

Abstract: Objectives: Systemic or local inflammation causes cardiac nerve sprouting and consequent arrhythmia. Metoprolol can prevent sympathetic nerve remodeling after myocardial infarction (MI), but the underlying mechanism is unclear. In this study, we evaluated the role of metoprolol in ameliorating sympathetic sprouting. Methods: Rabbits underwent ligation of the coronary artery for MI. MI rabbits received metoprolol or saline for 7 days. Immunohistochemistry was used to measure cardiac nerve sprouting and sympathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Previous studies have showed that dexamethasone [14], nicorandil [15], and metoprolol [13] can improve sympathetic nerve remodeling partly through down-regulating NGF. Infarct size is not significantly affected in resveratrol-treated infarcted rats which have a decreased NGF level [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have showed that dexamethasone [14], nicorandil [15], and metoprolol [13] can improve sympathetic nerve remodeling partly through down-regulating NGF. Infarct size is not significantly affected in resveratrol-treated infarcted rats which have a decreased NGF level [16].…”
Section: Discussionmentioning
confidence: 99%
“…Both endogenous and ectogenic up-regulation of NGF after MI can promote sympathetic nerve sprouting and hyper-innervation (neural remodeling) which contribute to arrhythmogenesis and sudden cardiac death [9][12]. Furthermore, several publications described that drug interventions improve sympathetic nerve sprouting and inhibite hyper-innervation partly by down-regulating myocardial NGF expression in infarcted hearts [13][16]. These findings indicate that modulation of NGF expression could regulate sympathetic innervation patterns, providing potential access points for novel therapeutic strategies to prevent lethal arrhythmias and sudden cardiac death.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, in the MI-SiRNA group, higher levels of NE were detected accompanied with a higher arrhythmic score and an increased incidence of inducible VAs. Previous studies revealed that sympathetic hyperinnervation and activation were correlated with a high incidence of lethal VAs and sudden cardiac death in post-infarcted hearts [ 5 , 7 , 8 , 30 ]. In addition, pro-arrhythmia effects were reported in sema 3A-related neural remodeling animals [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that metoprolol could inhibit ventricular remodelling and sympathetic nerve sprouting after MI by decreasing level of proinflammatory cytokines TNF-a and IL-1b and increasing level of anti-inflammatory cytokines IL-10. [25,26] Similarly, metoprolol could also have a positive therapeutic effect on MI rats by inhibiting proto-oncogene c-Fos. [27] Recently, miRNAs are emerged as drug targets for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%